Poster Edukatif sebagai Media dalam Meningkatkan Pemahaman dan Perilaku Cegah Stunting - Ratnasari Ratnasari; Hafsah Mukaromah; Sahrul Prayoga (Carmin: Journal of Community Service, 2025)
The Community Service Program of Aisyah University Pringsewu was held in Pekon Sinar Baru, Sukoharjo District, Pringsewu Regency, from 2 to 27 December 2024, as part of the implementation of the Tri Dharma of Higher Education. This program aims to provide real contributions in overcoming community problems, one of which is stunting in toddlers. Stunting prevention is carried out through counseling and socialization activities, utilizing educational poster media and PowerPoint presentations, held at the Sinar Baru Village Hall. This activity involved residents from four hamlets and health workers, with a total of 50 participants. This activity was conducted in four stages: preparation, counseling, poster installation, and evaluation. The preparation stage involves preparing educational materials and identifying community nutritional problems. Counseling focused on education about the importance of balanced nutrition, exclusive breastfeeding, complementary feeding, and supplements for pregnant women and toddlers. Educational posters were installed to visually and sustainably strengthen community understanding. Evaluation was conducted by distributing pre-test and post-test questionnaires, as well as participant satisfaction surveys. The results of the activity showed an increase in community knowledge about stunting and family nutrition, with a positive response from participants, including health cadres. This activity succeeded in encouraging collective awareness of the importance of early stunting prevention and strengthening synergy between students, the village government, and the community in efforts to improve the quality of children's health in Pekon Sinar Baru.